The Effect of Social Media, Hedonistic Behavior, and Emotional Intelligence on Financial Management among Students Living in Boarding Houses - Rabi'atul Afidah; Rosmida Rosmida (Universitas KH. Abdul Chalim Mojokerto, 2025)
Students living in boarding houses frequently encounter difficulties in managing their finances, which is often triggered by limited income, lifestyle demands, and intense exposure to digital platforms. Situations like these make financial management a crucial issue to examine, particularly when linked to psychological and behavioral factors that may influence it. This study investigates how social media use, hedonistic tendencies, and emotional intelligence shape the financial management practices of boarding house students, as well as compares the relative impact of each variable. The research applies a quantitative approach, utilizing questionnaires distributed to 100 respondents selected through purposive sampling. Data were analyzed using the Structural Equation Modeling method with Partial Least Squares (SEM-PLS). The findings reveal that social media exposure and hedonistic behavior do not significantly affect financial management, whereas emotional intelligence shows a strong, positive, and dominant influence in explaining students’ financial behavior. These results highlight that internal psychological traits play a more decisive role than external influences. Based on these insights, the study recommends that educational institutions incorporate emotional intelligence development into financial literacy programs and support students in enhancing their self-regulation skills for managing daily finances. Future research is advised to include mediator variables such as financial self-efficacy or self-regulation to broaden the understanding of factors influencing financial behavior.